The CAPM METHOD AS A TOOL FOR MEASUREMENT OF STOCK INVESTMENT EFFICIENCY - Nanang Rusliana; Salma Huda Aulia (LKP DCI, 2024)
In every investment decision, considerations such as financial information, calculations and adequate analyzes are required. This is necessary to choose stock investments that promise a level of profit with certain risks. If investors hope to obtain a high level of profit, then they must be willing to bear high risks as well. For this reason, investors should choose efficient shares in investing, namely shares that provide a certain level of profit with a minimum level of risk or that provide a certain level of risk with a maximum level of profit. CAPM is a model used to explain the relationship between systematic risk and profit levels. The expected profit is determined by the amount of systematic risk (beta), namely the sensitivity of a stock to the market. Stocks with a beta of more than one are stocks that are very sensitive to market growth, so they are called defensive stocks, namely stocks that are less sensitive to the market.